Genome-wide association analysis revealed genetic variation and candidate genes associated with the yield traits of upland cotton under drought conditions - Sun, Fenglei; Ma, Jun; Shi, Weijun; Yang, Yanlong (Frontiers in Plant Science, 2023)
Drought is one of the major abiotic stresses seriously affecting cotton yield. At present, the main cotton -producing areas in China are primarily arid and semiarid regions. Therefore, the identification of molecular markers and genotypes associated with cotton yield traits under drought conditions is of great importance for stabilize cotton yield under such conditions. In this study, resequencing data were used to conduct a genome-wide association study (GWAS) on 8 traits of 150 cotton germplasms. Under drought stress, 18 SNPs were significantly correlated with yield traits (single-boll weight (SBW) and seed (SC)), and 8 SNPs were identified as significantly correlated with effective fruit shoot number (EFBN) traits (a trait that is positively correlated with yield). Finally, a total of 15 candidate genes were screened. The combined results of the GWAS and transcriptome data analysis showed that four genes were highly expressed after drought stress, and these genes had significantly increased expression at 10, 15 and 25 d of fiber development. qRT-PCR was performed on two samples with drought tolerance extremes (drought-resistant Xinluzao 45 and drought-sensitive Xinluzao 26), revealing that three of the genes had the same differential expression pattern. This study provides a theoretical basis for the genetic analysis of cotton yield traits under drought stress, and provides gene resources for improved breeding of cotton yield traits under drought stress.